Lipid Profile of Children With Nephrotic Syndrome Admitted to a Tertiary Care Hospital: Lipid Profile in Nephrotic Syndrome - Zaman, Khaleda; Akter, Mst Asma; Khanam, Wahida; Sharifa, Tanjina; Adnan, Mohammad Ahad; Islam, Md. Azizul (Journal of Pediatric Nephrology, 2025)
Background and Aim: Hyperlipidemia is typically detected in active nephrotic syndrome (NS) and normalizes with the resolution of the proteinuria. This study assessed the lipid profile of children with NS during active disease and remission. Methods: This prospective observational study was conducted at ICMH, Bangladesh, from July 2021 to June 2022. Sixty children with NS (1-18 years), including both first attack and relapse cases, were enrolled. A detailed history and thorough clinical examination were carried out. Serum fasting lipid profiles were measured during active disease and again 4 weeks after achieving remission. After collecting all the required data, analysis was conducted using SPSS software, version 24.0. Results: The majority of children (70%) were relapse cases. The mean age of the study participants was 5.15±2.97 years, with a predominance of males (61.7%). Mean serum cholesterol, low-density lipoprotein (LDL), and triglycerides (TG) levels were elevated in all groups, while high-density lipoprotein (HDL) levels were normal in all groups during active disease. During remission, serum cholesterol, TG, and LDL levels were significantly reduced in both first attack and relapse cases. LDL levels returned to normal in all groups, but total cholesterol (TC) and TG remained high in the frequently relapsing NS (FRNS) and steroid-dependent NS (SDNS) groups. Serum albumin levels were low in all groups, with significantly lower levels observed in the FRNS group. Conclusion: During active disease, serum cholesterol, TG, and LDL levels were elevated in both first attack and relapse cases. Serum TC and TG remained persistently high in FRNS and SDNS.